High-frequency jet ventilation combined with endobronchial blocker for extraction of tracheal foreign body: a case report - Wei Liu; Yuanfang Liu; Yingbin Wang; Qihui Zheng (BMC Anesthesiology)
Abstract Background A foreign body (FB) in the airway is a potentially life-threatening clinical condition requiring prompt medical intervention. Due to the diverse nature of airway foreign bodies, distinct strategies should be tailored based on their types. Improper management may not only prevent successful removal but also endanger the patient’s life. In this case, we successfully removed a tracheal FB using high-frequency jet ventilation (HFJV) combined with an endobronchial blocker, thus providing clinicians with a novel approach for airway FB extraction. Case presentation We present the case of an 8-year-old girl admitted to the emergency room following accidental foreign body aspiration, accompanied by coughing and chest pain. Flexible bronchoscopy revealed a round foreign body above the carina. Attempts at oral removal failed due to the foreign body’s smooth surface. However, the foreign body was successfully removed with HFJV, which preserved the child’s spontaneous respiration. The procedure was performed under general anesthesia using remimazolam and remifentanil, along with an endobronchial blocker and rigid bronchoscopy. The patient had an uneventful recovery and was discharged on postoperative day 15, remaining asymptomatic with no sequelae at the 6-month follow-up. Conclusion Our case showed a novel approach to tracheal FB removal, which may improve success rates and reduce complications in select cases.